Legal Protection of Waqf Land That Is Not Registered at the Land Office - Teuku Ikhlasul Mufti; Ilyas, Ilyas; Adwani, Adwani (International Journal of Law and Society, 2025)
Article 19 paragraph (1) of Law Number 5 of 1960 concerning Basic Agrarian Principles "To ensure legal certainty by the government, land registration is carried out throughout the territory of the Republic of Indonesia according to the provisions regulated by government regulations". In fact, there are still many waqf lands that have not been registered with the National Land Agency (BPN), causing weak protection and legal certainty for waqf lands in Indonesia. This research uses normative juridical methods with regulatory and conceptual approaches. The results show that waqf land that is not registered with the national land agency has a weak position before the law, although religiously the waqf land that has been pledged is valid in sharia, but without official administration at the national land agency, the legal protection of waqf land is weak. The legal consequences of waqf land that is not registered with the national land office make the status of the waqf land still the previous property, because land registration is an administrative obligation that must be fulfilled to obtain legal certainty that is recognised in positive law by being registered with the National Land Agency. By not registering with the National Land Agency in accordance with the provisions of the law, the status of waqf land has not been registered as waqf asset land. It is recommended that the National Land Agency continue to socialise the importance of waqf land certificates and cooperate with the Indonesian Waqf Board and the Religious Affairs Office in its registration. It is also suggested that a regulation be made requiring nadhirs to report on waqf practices in the village every six months to record unregistered waqf land.